DIVERSITY AS A GENERAL BASIS OF TOURISM – SYSTEM APPROACH - Schejbal, Ctirad (GeoScience Engineering, 2015)
The general basis for tourism consists in the diversity of natural and man-made environment. The diversity can be considered as a natural characteristic of natural and anthropogenic systems produced by them as a condition of its continuance and development at all levels. When assessing tourism, geodiversity, biodiversity and socio-economic diversity, which includes technological diversity might be defined. Geodiversity and biodiversity coupled with technological diversity for the basis of geoscience and montanistic tourism. In the case of biodiversity, in terms of tourism regional and structural types of diversity are particularly important that can be parallelized with a geotope and a geophenomenon. The aim is to highlight the need for system approach to the analysis of tourism as a complex phenomenon with a complex structure.